2004
DOI: 10.1002/dev.20013
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations between child vagal tone and parenting behavior: 2 to 4 years

Abstract: The longitudinal relations between physiological markers of child emotion regulation and maternal parenting practices were examined from 2 to 4 years of age. At Time 1, cardiac vagal tone was assessed for one hundred four 2-year-olds (54 females); their mothers completed an assessment of parenting styles. Two years later, at Time 2, 84 of the original participants were reassessed on measures of cardiac vagal tone and parenting style. Results indicated both baseline cardiac vagal tone and maternal parenting pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 65 publications
4
76
1
1
Order By: Relevance
“…Stability in cardiac vagal tone has also been reported in infants and children from 9 months to 3 years (Porges et al, 1994b), 2 months to 5 years (Bornstein & Suess, 2000), and 2-to 4-years of age (Kennedy, Rubin, Hastings, & Maisel, 2004). Similar levels of stability have been found across a 2-year interval in children and young adolescents (El-Sheikh, 2004), and across shorter time intervals in adults (Byrne, Slater, & Porges, 1990;Hatch, Borcherding, & Norris, 1990).…”
Section: Frontal Electroencephalogram (Eeg) Asymmetrymentioning
confidence: 63%
“…Stability in cardiac vagal tone has also been reported in infants and children from 9 months to 3 years (Porges et al, 1994b), 2 months to 5 years (Bornstein & Suess, 2000), and 2-to 4-years of age (Kennedy, Rubin, Hastings, & Maisel, 2004). Similar levels of stability have been found across a 2-year interval in children and young adolescents (El-Sheikh, 2004), and across shorter time intervals in adults (Byrne, Slater, & Porges, 1990;Hatch, Borcherding, & Norris, 1990).…”
Section: Frontal Electroencephalogram (Eeg) Asymmetrymentioning
confidence: 63%
“…In addition, negative parenting (e.g., scolding, derogatory comments, controlling child's behavior) is associated with lower levels of RSA withdrawal in children during an emotional challenge (Calkins, Smith, Gill, & Johnson, 1998), and poor parent-child relationship quality also predicts lower levels of RSA withdrawal in toddlers . The relationship between parenting and RSA regulation in children may be reciprocal, for example, low withdrawal of RSA to stress in toddlers was shown to predict higher levels of negative parenting two years later (Kennedy, Rubin, Hastings, & Maisel, 2004).…”
Section: Rsa In Parent-child Interactionmentioning
confidence: 99%
“…Marital discord has been linked to lower vagal tone in infants (Porter et al, 2003) but higher vagal tone in preschoolers (Gottman and Katz, 1989). Burgess et al (2003) reported that avoidant attachment in infancy predicted high vagal tone for 4-year-old children, whereas Kennedy et al (2004) reported that child vagal tone at age 2 predicted more restrictive and less supportive parenting at age four. In the hypothalamic-pituitary-adrenal axis, quality of care is a moderator of physiological activity during a challenge .…”
Section: Contrary To the Cultural Model Maternal Factors Predict Chimentioning
confidence: 97%